2010
DOI: 10.1177/1010539510361515
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use Among Street Children and Non—Street Children in the Philippines

Abstract: This study characterizes the prevalence of drug use among Filipino street children compared with Filipino non-street children. A cross-sectional survey was administered to 311 street children and 528 non-street children aged 13 to 17 years. Participants were enrolled through 4 nonprofit organizations and 3 high schools located in Manila, Philippines. After adjustment for age and sex, street children with little or no contact with their families were 2.0 (95% confidence interval [CI] = 1.7-2.3) times more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
2
30
0
1
Order By: Relevance
“…Consistent with our findings, research conducted elsewhere found that street boys described having a moderate degree of awareness about the negative health outcomes associated with their use, yet they continued to use inhalants (Cottrell-Boyce, 2010; Kaime-Atterhög & Ahlberg, 2008; Morakinyo & Odejide, 2003; Njord et al, 2010; Seth et al, 2005). In contrast, a study in Egypt reported that very few children acknowledged that using volatile substances could negatively impact health (Elkoussi & Bakheet, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our findings, research conducted elsewhere found that street boys described having a moderate degree of awareness about the negative health outcomes associated with their use, yet they continued to use inhalants (Cottrell-Boyce, 2010; Kaime-Atterhög & Ahlberg, 2008; Morakinyo & Odejide, 2003; Njord et al, 2010; Seth et al, 2005). In contrast, a study in Egypt reported that very few children acknowledged that using volatile substances could negatively impact health (Elkoussi & Bakheet, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…These children spend either a portion or majority of their time on the street engaging in activities to generate income that often involve child abuse and exploitation (Bal, Mitra, Mallick, Chakraborti, & Sarkar, 2010), while falling into patterns of substance use (Bal et al, 2010; Morakinyo & Odejide, 2003; Njord, Merrill, Njord, Lindsay, & Pachano, 2010; Towe, ul Hasan, Zafar, & Sherman, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Street children worldwide adopt a wide range of risk behaviour, commonest of which include risky sexual practices, alcohol and substance abuse, and violence [8][9][10][11][12][13][14]. Extreme poverty, lack of appropriate care by adults, been victims of violence, and substance abuse have been repeatedly shown to be common determinants of delinquent and anti-social behaviour of street children [2,4,8].…”
Section: Introductionmentioning
confidence: 99%